PERUBAHAN POLA PERMUKIMAN MASYARAKAT BETAWI DI CONDET - Anisa Anisa; Jasrul Ilham; Tedy Purnama (Inersia : Jurnal Teknik Sipil dan Arsitektur, 2010)
Condet area located in District Kramat Djati has been declared as areas of cultural heritage since in 1976. In fact, each year in the region has been changing rapidly. Since a typical residential Batavia, loaded with fruit gardens, Condet turns into a dense residential area. This study aims to obtain along with changes in settlement patterns of Betawi Condet and the background’s factor. The research was conducted with descriptive exploratory to increase knowledge about the changes in patterns of settlement people Betawi in Condet and discover the factors influencing these changes. From this research found that homes used to have 1-2 hectares of gardens are now no longer exists. The houses built in recent decades is no longer a traditional Betawi house but modern houses and rented row house row. The factors that are behind them, among others, the factors of urbanization, economy, culture and behaviorof those who own Betawi.Keyword: Condet, cultural heritage, residential pattern, Kampung Betawi